Genetic polymorphism of lactic acid bacteria isolated from “Pirot ‘ironed’ sausage” from Serbia - Bogdanović, Svetlana; Jelušić, Aleksandra; Berić, Tanja; Nikolić, Ivan; Danilović, Bojana; Stanković, Slaviša; Dimkić, Ivica (Archives of Biological Sciences, 2019)
Paper description: Diversity of lactic acid bacteria (LAB) in six types of traditional “Pirot ‘ironed’ sausage” was determined. The morphological, biochemical and molecular characteristics of the isolates were tested. GTG5 PCR was determined as the best discriminatory technique for fast LAB screening. Lactobacillus sakei and Leuconostoc mesenteroides were the dominant species. High genetic heterogeneity of L. sakei isolates could be important for the specific nature of the sausage. Abstract: The “Pirot ‘ironed’ sausage” (Pis) is a traditional, dry, fermented product originating from the town of Pirot, situated in southeastern Serbia. This product is made from different types of meat (goat, sheep, beef and donkey) and spices, without additives or starter cultures. Pis is an organic, unprocessed product, without heat or smoke treatment. The aim of this study was to characterize 120 isolates of lactic acid bacteria (LAB) from Pis produced by six different brands during a two-year period using phenotypic and genetic identification. Preliminary characterization of the LAB was based on general morphology and biochemical tests. Repetitive elements such as REP, BOX and GTG5, found in the genome of these bacteria, and randomly amplified polymorphic DNA-polymerase chain reaction (RAPD PCR) sequences were used for determination of genetic polymorphism. Identification by 16S rRNA gene sequencing showed the presence of only two LAB species, Lactobacillus sakei (76%) and Leuconostoc mesenteroides (24%). However, genetic polymorphism was detected using fingerprinting methods. In comparison with other primers, the profiles obtained with GTG5 showed the highest heterogeneity for most of the tested isolates, with sequencing results additionally confirming its discriminatory power. In addition, M13 RAPD primer also produced satisfactory separation of the tested isolates. https://doi.org/10.2298/ABS180920051B Received: September 20, 2018; Revised: October 31, 2018; Accepted: November 5, 2018; Published online: November 6, 2018; Published online: November 9, 2018 How to cite this article: Bogdanović S, Jelušić A, Berić T, Nikolić I, Danilović B, Stanković S, Dimkić I. Genetic polymorphism of lactic acid bacteria isolated from “Pirot ‘ironed’ sausage” from Serbia. Arch Biol Sci. 2019;71(1):95-102.